0374 Decline in Habitual Sleep Duration Over 10 Years and Worsening Sleep Disparities: Data From NHIS (2006-2015). (27th May 2020) - Grandner, M A; Fernandez, F; Khader, S; Jean-Louis, G; Seixas, A A; Williams, N J; Patterson, F; Killgore, W D; Wills, C C
Abstract: Introduction: Despite claims in the media, evidence that habitual sleep has declined in recent years is scant. Few data sources exist that systematically document sleep duration in a nationally representative sample, in the same way, over several years. Methods: Data from 10 years of the National Health Interview Survey were used (N=305, 555). During all years, habitual sleep duration, age, sex, race/ethnicity, and height/weight were recorded in the same way. Weighted regression analyses examined sleep duration as the outcome, year as linear predictor, and sociodemographics as covariates. Then, interaction terms examined whether the linear change associated with years was differentially experienced by different sociodemographic groups. Results: The linear trend of sleep duration over the past 10 years is a loss of 0.78 minutes per year (95%CI -0.91, -0.64; p<0.0001). After adjustment for age, sex, race/ethnicity and BMI, this remained relatively unchanged at 0.86 minutes (95%CI -0.99, -0.73; p<0.0001). A year-by-race/ethnicity interaction was observed (p<0.05). In stratified analyses, Non-Hispanic Whites showed a loss of 0.68 minutes per year (95%CI -0.84, -0.52, p<0.0001). This was 1.33 minutes/year in Blacks/African-Americans (95%CI -1.74, -0.92; p<0.0001), 1.57 minutes/year in Mexican-Americans (95%CI -1.98, -1.16; p<0.0001), 0.99 minutes/year in other Hispanics/Latinos (95%CI -1.51, -0.47; p<0.0001), 0.74 minutes/year in Asians (95%CI -1.24, -0.25; p=0.003), and 1.80 minutes/year in American Indians/Alaskan Natives (95%CI -3.57, -0.03, p=0.046). Conclusion: On average, the US population has lost 47 seconds of nightly sleep per year over a 10-year period, equating to about 4.7 hours of sleep per year, but racial/ethnic groups were impacted differently. Compared to Non-Hispanic Whites, Blacks/African-Americans lost 96% more sleep, Mexicans lost 131% more sleep, other Hispanics/Latinos lost 46% more sleep, Asians lost 9% more sleep, and American Indians lost 165% more sleep. Thus, sleep disparities may be widening. Support: Dr. Grandner is supported by R01MD011600